Answer:
x1= -4
x2 = 4
Step-by-step explanation:
Set the equation equal to zero
x2 − 16 = 0
then
(x + 4)(x − 4) = 0
(x+4)= 0 which is equal to -4
and
(x-4)= 0 equals 4
Answer:
52 feet apart
Step-by-step explanation:
20 + 32 = 52
Answer:
-3
Step-by-step explanation:
-3/8÷3/4
=-3/8×4/3
=-6/2
=-3
Answer:
Step-by-step explanation:
Gradient of a line =( y2 - y1)/x2 - x1
From the question, x1=4,y1=-1,x2=1,y2=0.
Therefore, substitute for these values in the above formula
m = 0-(-1)/1-4
= 0+1/-3
= -1/3.
Therefore, y-y1/x-x1 = -1/3
y - y1 = -1/3(x - x1)
y - (-1) = -(x-x1)/3
y+1 = - (x - 4)/3
Multiply through by 3
3y+3= -x+4
3y +x=4-3
x+3y= 1
Therefore the answer is A.
To answer this question, you need to multiply the number inside the bracket first. Then you can move the number to the right side of the equal sign and keep the x on the left side of the equal sign. The step would be like this
2(x – 5) - 6x= -22(2x - 10) - 6x = -222x - 6x = -22 +10-4x= -12x= -12/-4x=3
Hope this helps!!!